Genital Chlamydia trachomatis and Neisseria gonorrhoeae infections among women in sub-Saharan Africa: A structured review. (July 2018) - Dubbink, Jan Henk; Verweij, Stephan P; Struthers, Helen E; Ouburg, Sander; McIntyre, James A; Morré, Servaas A; Peters, Remco PH
Chlamydia trachomatis and Neisseria gonorrhoeae constitute major public health problems among women, but the burden of infection in sub-Saharan Africa is poorly documented. We conducted a structured review of the prevalence and incidence of genital, oral and anal C. trachomatis and N. gonorrhoeae infection in women in sub-Saharan Africa. We searched Medline, EMBASE and Web of Science over a 10-year period for studies on epidemiology of genital, oral and anal chlamydial infection and gonorrhoea in women in all countries of sub-Saharan Africa. We assessed geographic and demographic differences in prevalence and incidence of infection; weighted mean prevalence estimates were calculated with a random-effect model. A total of 102 study results were included, with data available for 24/49 of sub-Saharan countries. The weighted prevalence of chlamydial infection was lower among women in community-based studies (3.9%; 95% CI: 2.9–5.1%) than for women recruited at primary healthcare facilities (6.0%; 95% CI: 4.2–8.4%, p < 0.001); the same was observed for gonorrhoea (2.2%; 95% CI: 1.2–4.0% vs. 4.2%; 95% CI: 3.2–5.6%, p < 0.001). Prevalence of Chlamydia among sex workers was 5.5% (95% CI: 4.2–7.3%) and gonorrhoea 7.6% (95% CI: 5.4–11%). Seven studies reported on incidence which varied between 0.75–28 and 2.8–17 per 100 person-years-at-risk for chlamydial infection and gonorrhoea, respectively. Only two studies reported on anal infections and one on oral infection. This overview underscores the considerable incidence and prevalence of genital C. trachomatis and N. gonorrhoeae in women in different settings in sub-Saharan Africa. Better control strategies are warranted to reduce the burden of infection and to prevent long-term complications of these infections.